Mechanized Method for the Removal and Disposal of Stones on Mountain Slopes - S. M. Dzhibilov; L. R. Gulueva (Сельскохозяйственные машины и технологии, 2020)
To remove medium and large stones from mountain meadows and pastures with an exposure slope of up to 12 degrees, a new method and prototype machine were developed. The authors showed that the machine removes 95 percent of the stones. The machine efficiency was determined by new working bodies: a rotary frame, a comb and a special plow that cut a channel along the movement of the machine. (Research purpose) To substantiate the design parameters of a mountain stone-harvesting machine and their impact on the grassland preparation quality.  (Materials and methods) The machine was tested on the southern slope of the Dargavskoy Basin of North Ossetia-Alania at an altitude of 1650 meters above sea level, with a slope of 12 degrees. There were 9 options (3 in each repetition), each second option was a control one. (Results and discussion) A method and a machine for removing stones with a diameter of more than 30 millimeters on slopes with a steepness of up to 12 degrees were developed. It was determined that stone clogging as the options were located from top to bottom averaged 37.2; 45.6 and 52.0 percent of the plot area. (Conclusions) It was established that an increase in the pastures useful area due to the removal and utilization of stones made it possible to increase the load on 1 hectare of pastures, from 1.1 to 3.6 heads of feeding young cattle. The authors showed that the machine, along with the removal of stones, evenly distributed animal excrement, thereby increasing the productivity of fodder land: productivity compared to control increased annually by 0.33-1.93 tons per hectare.